Mensageria Descentralizada como Infraestrutura Pública: Uma Perspectiva sobre a Web3 como Bem Comum Digital - Viegas, Fabrício Barbosa; Salem, Murilo Costa; Tavares, Tatiana Aires (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2025)
Digital messaging plays a central role in modern society, but it is currently dominated by centralized platforms that compromise user privacy and control. This position paper argues that decentralized messaging systems, based on open protocols and free software, can serve as public communication infrastructure and exemplify Web3 as a digital common good. We discuss the limitations of current services (identity lock-in, user fragmentation, data exposure) and present decentralized approaches (peer-to-peer, federated, blockchain-based) according to recent literature. We relate these models to the concept of public digital infrastructure, essential communication systems managed in a non-exclusive manner, and the notions of digital commons. As illustrative cases, we cite open protocols like Matrix and Web3 initiatives that adopt blockchain-based identity (e.g., XMTP), showing that such systems exhibit the characteristics of common resources: public specification, collective governance, and open-source software.